The Impact of Digital Therapeutics on Current Health Technology Assessment Frameworks - Yan, Kevin; Balijepalli, Chakrapani; Druyts, Eric (Frontiers in Digital Health, 2021)
Historically healthcare has been delivered offline (e.g. physician consultations, mental health counselling services). It is widely understood that healthcare lags behind other industries (e.g. financial, transportation) whom have already incorporated digital technologies in their workflow. However, this is changing with the recent emergence of digital therapeutics (DTx) helping to bring healthcare services online. To promote adoption, healthcare providers need to be educated regarding the digital therapy to allow for proper prescribing. But of equal importance is affordability and many countries rely on reimbursement support from the government and insurance agencies. Here we briefly explore how national reimbursement agencies or non-profits across six countries (Canada, United States of America, United Kingdom, Germany, France, Australia) handle DTx submissions and describe the potential impact of digital therapeutics on current health technology assessment (HTA) frameworks.